Sexual and gender based violence in armed conflicts: problems of defining and creating a prevention mechanism - Karvatska, Svitlana; HNATIUK, Tetyana; Labyk, Anastasia (Baltic Journal of Legal and Social Sciences, 2024)
In this comprehensive analysis, the article delves into the multifaceted nature of gender-based violence, highlighting its impact on individuals' health, development, and identity, primarily stemming from entrenched gender inequalities. It underscores the challenge in documenting and prosecuting such violence, exacerbated by stigmatization and access barriers to essential services for survivors. The study emphasizes the role of key international human rights documents, like the UN Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), in advocating for gender equality and safeguarding human rights and fundamental freedoms. Through a review of scholarly work and an examination of the current state of gender-based violence in conflict zones, the article identifies a pressing need for mechanisms to prevent and address such violence effectively. It critically assesses the role of international legal frameworks and the Geneva Conventions in establishing accountability and protective measures for women, while also recognizing the persistent issues of impunity and the complex factors contributing to sexual violence in conflicts, including power dynamics and systemic vulnerabilities. The article advocates for enhanced legal and institutional responses at both national and international levels to bridge the gap between law and reality, proposing the establishment of an International Gender Unit as a proactive measure towards integrating gender perspectives into peace and security policies. Finally, it calls for concerted efforts to enforce the prohibition of sexual violence, underscoring the necessity of global and localized action
Keywords: sexual violence; international humanitarian law; international human rights law; international criminal law; crimes against humanity; acts of genocide